Effect of task complexity and time pressure on auditor performance with compensation and organizational citizenship behavior (OCB) as moderation - Adnyana, I Wayan; Mimba, Ni Putu Sri Harta (International research journal of management, IT and social sciences, 2019)
This study aims to examine the effect of task complexity and time pressure on auditor performance at the Public Accounting Firm (KAP) in Bali Province with compensation and organizational citizenship behavior (OCB) as moderating. The population in this study were all KAP auditors in Bali Province registered in the Directory published by the Indonesian Institute of Certified Public Accountants (IAPI) in 2017. The sampling technique used was purposive sampling. The criteria are: the auditor works in a KAP throughout the Province of Bali who is still actively operating and has a minimum work period or audit experience of 1 year. 61 questionnaire data were processed. The results of this study found that: task complexity has a negative effect on auditor performance, time pressure has a negative effect on auditor performance. The results also show that compensation is not able to moderate the influence of task complexity and time pressure on auditor performance. Organizational citizenship behavior (OCB) is not able to moderate the influence of task complexity on auditor performance but is able to moderate the influence of time pressure on auditor performance.